2019
DOI: 10.1155/2019/8092865
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Short Physical Performance Battery Frailty Index to Predict Mortality and Hospital Readmission in Patients with Liver Cirrhosis

Abstract: Background/Aims. Unplanned hospitalisation is a marker of poor prognosis and a major financial burden in patients with cirrhosis. Frailty-screening tools could determine the risk for unplanned hospital admissions and death. The study aims to evaluate the bedside frailty-screening tool (Short Physical Performance Battery (SPPB)) in prediction of mortality in patients with liver cirrhosis. Methods. One hundred forty-five patients with liver cirrhosis were recruited from Cairo University Hospital. Clinical assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…used another physical function test, the Short Physical Performance Battery (SPPB), and reported that the SPPB is not associated with the muscle mass of patients with CLD . SPPB consists of walking speed, standing balance, and timed chair stands . It remains unclear as to why no association was seen between SPPB and muscle mass, a possible reason is that walking speed, but not grip strength, is used as an assessment item in SPPB.…”
Section: Discussionmentioning
confidence: 99%
“…used another physical function test, the Short Physical Performance Battery (SPPB), and reported that the SPPB is not associated with the muscle mass of patients with CLD . SPPB consists of walking speed, standing balance, and timed chair stands . It remains unclear as to why no association was seen between SPPB and muscle mass, a possible reason is that walking speed, but not grip strength, is used as an assessment item in SPPB.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SPPB has high clinical utility in a diverse range of clinical populations. 22 26 The 2-minute step test was selected for endurance because of its utility in acutely ill and active populations and because the testing conditions, like step height, could be varied and exercise capacity and metabolic equivalent of task level performance could be calculated to illustrate progress, as functional capacity improved. 20…”
Section: Selection Of the Core Outcome Measuresmentioning
confidence: 99%
“…The studies that were assessed were exclusively observational or cohort studies, with no defined interventions in any of the studies. Using the suitable quality assessment tool, 31 only one of these studies 32 was highlighted as poor quality.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown to be predictive of both frailty and waitlist mortality in patients awaiting a liver transplant 37 . Four of the included 12 studies prospectively utilised SPPB in their assessment and demonstrated that it could predict mortality 32,34,35,38 . Essam Behiry et al 32 demonstrated through ROC curve analyses of mortality based on frailty as per SPPB, handgrip, MELD and Childs‐Pugh that only SPPB had a significant AUC (0.743; p = 0.013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation